Potensi Cendawan Endofit Asal Jahe Merah (Zingiber officinale Roscoe) untuk Mengendalikan Cendawan Patogen Candida albicans In Vitro: Potency of Endophytic Fungi Isolated From Zingiber officinale Roscoe to Control Pathogenic Fungus Candida albicans In Vitro - Sari, Mulya; Sukarno, Nampiah; Batubara, Irmanida; Cinta Badia Br Ginting, Rohani (Jurnal Sumberdaya Hayati, 2020)
Endophytic fungi isolated from red ginger (Zingiber officinale) can inhibit growth of Fusarium oxysporum, but the ability of the fungi to control Candida albicans as human pathogen has not been reported. The aims of this research were to study the mechanism of ten endophytic fungi isolates derived from red ginger to control C. albicans in vitro using dual culture methode and fungal extract, and to determine fungal bioactive chemical groups produced by the fungi. Three out of ten isolates tested, Talaromyces assiutensis JMa 7, T. assiutensis JMbt 3, and Curvularia affinis JMbt 9 inhibited growth of C. albicans with inhibition zones were 4.0 mm, 4.9 mm, and 11.3 mm, respectively. The cultures of the three potential endophytic fungi were extracted by maceration method using 3 solvents i.e ethyl acetate, n-hexane and ethanol. The three isolates were grown in PDB separately for 21 days incubation. At harvest, the culture filtrate was extracted by ethyl acetate and n-hexane, while fungal mycelia were extracted by all the three solvents. Ethyl acetate extracts obtained from culture filtrate of all the three fungal isolates consistently inhibited C. albicans with inhibition zones were 2.0-3.8 mm. For n-hexane extract, however, only Talaromyces assiutensis JMbt 3 that had positive effect with inhibition zone was 2.0 mm. All extracts from mycelia did not have any effects on C. albicans. The ethyl acetate extract of T. assiutensis JMbt 3 was analysed to determine its chemical groups using visible color on thin layer chromatography (TLC). The results showed that the bioactive compounds was terpenoids, and antioxidant.